Lessons Learned in the Early Stages of a Community-Academic Partnership to Address Health Disparities in a Rural Community - Tiffany Washington; Brian Rivers; L. Raleigh; Natalie Hernandez; Mindy Le; A. Green; Jeffery Lawrence; Henry Young (Georgia Southern University, 2020)
In rural Georgia, African American men are burdened by chronic health diseases such as cancer, diabetes, and cardiovascular disease. Community-academic partnerships that leverage community-based participatory research (CBPR) principles can facilitate the adaptation and translation of multilevel programs to address chronic disease prevention and management in rural areas. The objective of this study was to explore key components of the CBPR process that bolstered the early stages of a partnership established between rural-residing community leaders and academic partners in Georgia. Qualitative methodology was used to collect and assess data regarding the initial engagement between the community and academic partners. Findings indicate that five components supported initial engagement: utilizing the public service and outreach arm of the university to connect with rural communities; creating synergy around identified community health needs; encouraging community members to provide input into the research design to ensure the research goals reflect community values; enhancing the capacity of community partners; and following the lead of the community. Findings provide insights into how to begin engaging rural communities in the southeast in order to strengthen the adaptation and translation of initiatives to improve cancer, diabetes and cardiovascular disease outcomes.